Moderating influence of government policy on relationship between entrepreneurship education and business start up of undergraduate business education students in North East Nigeria - Adamu, I. A.; Bello, H.; Dalhat, B. S.; Inti, M. M. (Kashere Journal of Education, 2023)
The study aimed at determining the Moderating Influence of Government Policy on Relationship Between Entrepreneurship Education and Business Start-Up of Undergraduate Business Education students in Nigeria. Survey was used for the study; the population of the study comprises 998 final year undergraduates’ business education students. Stratified proportionate sampling technique was used for the study. Instrument used for data collection was a structured questionnaire. Reliability of the instrument was determined using Cronbach Alpha to test the internal consistency of the instrument. The data was collected by the researcher with the help of research assistants. Data collected was analyzed using Statistical Package of Social Science (SPSS, 25). The findings of the study revealed that Entrepreneurial mind set does not significantly influence business startup of undergraduate business education students and also Government policy does not significantly moderate the relationship between, entrepreneurial mind set on business startup. Based on this the study recommended among others that, Lecturers in the universities should ensure entrepreneurship education is directed toward inculcating, and instilling, entrepreneurial mind-set for business start-up of undergraduate business education students of federal universities in North-east, Nigeria.